Differentiating heart failure phenotypes using sex‐specific transcriptomic and proteomic biomarker panels. (4th March 2017) - Toma, Mustafa; Mak, George J.; Chen, Virginia; Hollander, Zsuzsanna; Shannon, Casey P.; Lam, Karen K.Y.; Ng, Raymond T.; Tebbutt, Scott J.; Wilson‐McManus, Janet E.; Ignaszewski, Andrew; Anderson, Todd; Dyck, Jason R.B.; et al.
Abstract: Aims: Heart failure with preserved ejection fraction (HFpEF) accounts for 30–50% of patients with heart failure (HF). A major obstacle in HF management is the difficulty in differentiating between HFpEF and heart failure with reduced ejection fraction (HFrEF) using conventional clinical and laboratory investigations. The aim of this study is to develop robust transcriptomic and proteomic biomarker signatures that can differentiate HFpEF from HFrEF. Methods and results: A total of 210 HF patients were recruited in participating institutions from the Alberta HEART study. An expert clinical adjudicating panel differentiated between patients with HFpEF and HFrEF. The discovery cohort consisted of 61 patients, and the replication cohort consisted of 70 patients. Transcriptomic and proteomic data were analysed to find panels of differentiating HFpEF from HFrEF. In the discovery cohort, a 22‐transcript panel was found to differentiate HFpEF from HFrEF in male patients with a cross‐validation AUC of 0.74, as compared with 0.70 for N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) in those same patients. An ensemble of the transcript panel and NT‐pro‐BNP yielded a cross‐validation AUC of 0.80. This performance improvement was also observed in the replication cohort. An ensemble of the transcriptomic panel with NT‐proBNP produced a replication AUC of 0.90, as compared with 0.74 for NT‐proBNP alone and 0.73 for the transcriptomic panel. Conclusions: We have identified a male‐specific transcriptomic biomarker panel that can differentiate between HFpEF and HFrEF. These biosignatures could be further replicated on other patients and potentially be developed into a blood test for better management of HF patients.